The Effect of Using Some Educational Technologies on Learning the Artistic Performance and Achievement Level in Shot Putting - Majeed Fulaeh Hassan (College of Physical Education and Sport Sciences, 2020)
The research aimed at finding the differences between pre and posttests in experimental groups in learning artistic performance and achievement in shot putting as well as finding the differences between posttests in groups. The researchers used the experimental method (pre-post) tests on (50) first year college of physical education and sport sciences/ university of Samarh (18) applying teaching video technology, (18) applying posters, and (10) pilot study students. The data was collected and treated using SPSS to conclude that using teaching technology in learning artistic performance and achievement level in shot putting is very effective in addition that there are significant differences between pre and posttests in learning artistic performance and achievement level in shot putting in favor of posttest.